2019
DOI: 10.1002/pon.5013
|View full text |Cite
|
Sign up to set email alerts
|

Fear of cancer recurrence in adolescent and young adult cancer survivors: A systematic review of the literature

Abstract: Objective The current systematic review aims to provide an overview of fear of cancer recurrence (FCR) in adolescent and young adult cancer survivors (15‐39 years at cancer diagnosis, AYAs). Methods MEDLINE, PubMed, PsycINFO, and Embase databases were independently searched to identify relevant quantitative articles. PRISMA systematic review procedures were followed with quality assessment. Results Seventeen studies were included in the current review. All were quantitative studies that utilized a cross‐sectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
68
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 92 publications
(77 citation statements)
references
References 61 publications
(247 reference statements)
8
68
0
1
Order By: Relevance
“…Between 69 and 75% reported some degree of FCR and approximately 20% reported quite a bit or a lot of worry concerning disease recurrence or getting another cancer in this large population of long-term survivors. Previous studies on Table 2 Fear of cancer recurrence (FCR) in the total sample, according to diagnostic group and cancer worry item in the Assessment of Survivorship Concern (ASC) Scale, and as a summed score, in total and according to diagnostic group ASC item N (%) MM 1 (%) BC 2 (%) CRC 3 (%) NHL 4 (%) LEU 5 3 Colorectal cancer 4 Non-hodgkin lymphoma 5 Leukemia 6 3 missing values for this item 7 1 missing value for this item 8 Standard deviation 9 Confidence interval FCR among AYA cancer survivors, which typically have shorter observation times, report prevalence estimates in the range of 31-85% [7,11]. The heterogeneity of both samples and FCR measures used makes comparison across studies challenging.…”
Section: Discussionmentioning
confidence: 99%
“…Between 69 and 75% reported some degree of FCR and approximately 20% reported quite a bit or a lot of worry concerning disease recurrence or getting another cancer in this large population of long-term survivors. Previous studies on Table 2 Fear of cancer recurrence (FCR) in the total sample, according to diagnostic group and cancer worry item in the Assessment of Survivorship Concern (ASC) Scale, and as a summed score, in total and according to diagnostic group ASC item N (%) MM 1 (%) BC 2 (%) CRC 3 (%) NHL 4 (%) LEU 5 3 Colorectal cancer 4 Non-hodgkin lymphoma 5 Leukemia 6 3 missing values for this item 7 1 missing value for this item 8 Standard deviation 9 Confidence interval FCR among AYA cancer survivors, which typically have shorter observation times, report prevalence estimates in the range of 31-85% [7,11]. The heterogeneity of both samples and FCR measures used makes comparison across studies challenging.…”
Section: Discussionmentioning
confidence: 99%
“…110 Fear of recurrence is also high, with up to 62% reporting elevated worry. 112 Notably, distress symptoms have been found to persist beyond treatment completion, with the highest levels documented within the first 2 years after treatment completion. 113 It is also important to note that, given the timing of their diagnosis, symptoms of distress may fluctuate and coincide with key developmental milestones affected by cancer.…”
Section: Transitioning Into Post-treatment Survivorship: Addressing Pmentioning
confidence: 99%
“…As well, multiple studies have found that younger women are more prone to high FCR than older women . Elevated FCR in young people is associated with lower physical and psychological functioning and lower overall quality of life . Due to its far‐reaching consequences, it is important to adequately screen for FCR with scales that are both psychometrically sound and practical to use in a clinical setting.…”
Section: Introductionmentioning
confidence: 99%